Biscuit Goes to School - Capucilli, Alyssa Satin (United States : Harper Collins Publisher, 2002)
A dog follows the bus to school, where he meets the teacher and takes part in the activities of the class.
Keywords: Dogs -- Fiction; School -- Fiction